Boron-nitrogen coordination functionalized main-chain cationized n-type organic ion-electron hybrid conductor material and preparation and application thereof

CN122897969APending Publication Date: 2026-10-13FUDAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610938469.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

侧链的大量引入会严重破坏聚合物的规整堆积与结晶度,导致电子迁移率大幅度下跌

Benefits of technology

离子-电子传输通道的协同构筑:互通的多孔通道为水相生物离子(如Na+、Cl-)提供了几乎无阻碍的宏观快车道,使其能瞬间渗透至活性层全域,极大地促进了电荷存储能力;而其内部超紧密的π-π共轭堆积则确保了电子的高速跳跃传导,一定程度上解决了传统材料“离子渗透增大则电子迁移率暴跌”的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897969A_ABST
    Figure CN122897969A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of organic polymer semiconductor materials and integrated device, and particularly relates to n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization and preparation and application thereof. The present application utilizes the inner coordination reaction between bidentate nitrogen-containing heterocycle (bipyridine or bipyrazine) and boron trifluoride to directly form strong electron-deficient construction unit cationization, and alternately copolymerizes with donor unit connected with polar hydrophilic oligomeric ethylene glycol side chain. The main chain cationization greatly deepens the LUMO energy level of the polymer (up to-3.96 eV or below), and endows the material with excellent electrochemical working stability in water and oxygen environment. In addition, combined with the mixed solvent processing strategy, the strong hydrogen bond network between the polymer main chain and the solvent is dissociated, and a three-dimensional porous network micro-morphology interpenetrating each other can be spontaneously constructed in the film, and at the same time, the close π-π stacking (3.55 angstrom) between the skeleton molecules is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic polymer semiconductor materials and integrated devices, and in particular to n-type organic ion-electron hybrid conductor materials based on boron-nitrogen coordination functionalized main chain cationization, their preparation and application. Background Technology

[0002] Bioelectronics bridges a crucial physical gap between living organisms and traditional solid-state electronic devices. Developing flexible electronic devices capable of real-time, highly sensitive detection and recording of weak electrochemical signals, biomolecular changes, or physiological processes within the body is of great significance for precision medicine, health monitoring, and intelligent diagnosis. Organic electrochemical transistors (OECTs), as a novel type of three-terminal flexible switching and amplifying device, operate by driving ions from the electrolyte into the active layer of the channel through a gate voltage. This causes electrochemical doping and dedoping across the entire active layer, significantly modulating the conductivity of the channel layer. Thanks to this three-dimensional global doping effect, OECTs can convert weak biological ion signals into significant electrical signals, exhibiting extremely high transconductance. g m ) and signal amplification capability.

[0003] The core of an OECT device is the active layer material: organic ion-electron hybrid conductors (OMIECs), which must simultaneously possess excellent electronic conductivity (mobility). μ ) and high ion permeation / adsorption storage capacity (volume specific capacitance) C The overall performance of a device is determined by its quality factor. μC The decision has been made. Currently, based on charge carrier type, OMIECs are mainly divided into p-type (hole transport) and n-type (electron transport). Similar to the development trajectory of field-effect transistors, p-type materials are now mature, and their quality factor has exceeded several hundred F / cm². -1 V -1 s -1However, the development of n-type OMIECs materials has lagged significantly, becoming a major bottleneck in the development of flexible complementary organic circuits and biosensors. This is mainly because: ① The main chain of traditional n-type mixed-conductivity materials is intrinsically strongly hydrophobic, often requiring the introduction of a large number of polar hydrophilic side chains (such as oligoethylene glycol OEG). The large-scale introduction of side chains severely disrupts the regularity and crystallinity of the polymer, leading to a significant drop in electron mobility. ② The acceptor units of existing n-type materials have insufficient electron-withdrawing ability, resulting in a high least unoccupied molecular orbital (LUMO) energy level. In aqueous, oxygen-rich biological operating environments, high LUMO energy level materials are easily oxidized by water and oxygen, leading to unstable device operation and high doping voltage. ③ The film morphology of traditional nonionic materials is dense, and the diffusion rate of aqueous ions within it is slow, resulting in low volumetric capacitance. C low.

[0004] In recent years, some studies have attempted to introduce charged ionic groups into the side chains to form ionic polymers. However, strong electrostatic repulsion and steric hindrance lead to severe distortion of the main chain, further deteriorating carrier mobility. Therefore, how to maintain a highly ordered main chain arrangement and deepen the LUMO energy level while in situ endowing the material with excellent hydrophilicity and porous ion transport channels is a highly challenging scientific problem in this field. Summary of the Invention

[0005] To address the aforementioned problems, the present invention aims to provide an n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination-functionalized main chain cationization, its preparation, and applications. This invention utilizes a bidentate nitrogen-containing heterocycle (bipyridine or bipyrazine) to undergo an internal coordination reaction with boron trifluoride, directly forming a cationized strongly electron-deficient building block, which is then alternately copolymerized with donor units attached to polar hydrophilic oligoethylene glycol side chains. Main chain cationization significantly deepens the polymer's LUMO level (down to below -3.96 eV), endowing the material with excellent electrochemical stability in water and oxygen environments. Furthermore, by combining a mixed solvent processing strategy, the strong hydrogen bond network between the polymer main chain and the solvent dissociates, spontaneously constructing an interconnected three-dimensional porous network microstructure within the film, while achieving tight π-π packing (3.55 Å) between its framework molecules. This porous film exhibits extremely high ion permeation channels and electron mobility, with a normalized transconductance of 38.9 Scm in the constructed organic electrochemical transistor (OECT). -1 Quality factor μC Reaching 215.9 F cm -1 V -1 s -1 The material of this invention exhibits extremely high detection sensitivity and signal-to-noise ratio in flexible wearable bioelectrical signal sensors such as electrocardiograms (ECG), and has broad prospects for industrialization.

[0006] The core design of this invention is as follows: Utilizing boron trifluoride (BF3), a Lewis acid with strong forward electron-withdrawing ability, and the sp... 2 The lone pair electrons of the hybrid nitrogen atom undergo efficient coordination. This strategy possesses the following unique physicochemical mechanisms and technological advantages: Extremely high main-chain planarity and rigidity: B←N internal coordination forms a stable rigid chelate ring on the main chain, greatly enhancing the conformational torsion barrier between adjacent heterocycles (calculations show that the conformational transition barrier is >30 kcal / mol). -1 This endows the polymer skeleton with excellent planar regularity.

[0007] Deeper LUMO levels: Due to the partially negative charge of neutral boron atoms and the transformation of coordinating nitrogen atoms into positively charged cation centers, a high-density positive charge aggregation region resembling an internal salt of fluorine-boron-nitrogen is formed throughout the main chain. This extremely strong electron-withdrawing effect causes the LUMO level of the polymer to shift to a lower depth (PBPyBF3 reaches -3.71 eV, PBPzBF3 reaches -3.96 eV and even -4.10 eV). The low energy level perfectly avoids the electrochemical potential of water-oxygen oxidation, endowing the material with intrinsically ultra-high aqueous phase working stability and a low threshold injection voltage.

[0008] The intrinsic porous network morphology induced by hydrogen bonding: The exposed positively charged centers of the main chain and the strongly electronegative fluorine (F) atoms on the periphery enable it to form a dynamic hydrogen bond cross-linking network with solvent molecules and trace amounts of undesirable solvents (ethylene glycol dimethyl ether, DME) when processed with strong hydrogen bond donor solvents such as hexafluoroisopropanol (HFIP). During spin-coating thermal desorption, along with hydrogen bond dissociation and in-situ solvent evaporation, a large-area, highly interconnected three-dimensional micro / nano porous network automatically emerges in situ within the film.

[0009] The objective of this invention can be achieved through the following technical solutions: The first objective of this invention is to provide an n-type organic ion-electron hybrid conductor (OMIECs) material based on boron-nitrogen coordination-functionalized backbone cationization, having a conjugated backbone composed of alternating copolymerization of electron acceptor units and electron donor units, the chemical structure of which is shown in formula (I): Formula (I); Where X and Y are each independently selected from carbon, nitrogen, oxygen or sulfur; Z is selected from fluorine, chlorine, bromine or cyano; Ar represents aryl, heteroaryl or other conjugated groups; n represents the degree of polymerization of the polymer; The number-average molecular weight (Mn) of n-type organic ion-electron hybrid conductor materials is >10 kDa.

[0010] In one embodiment of the present invention, the electron acceptor unit is a cationized bipyridine or cationized bipyrazine structure locked by a boron-nitrogen (B←N) coordination bond; Ar is a thiophene-substituted pyrrolopyrroledione (DPP) derivative structure, and the nitrogen atom of pyrrolopyrroledione is attached with a branched oligoethylene glycol (OEG) polar hydrophilic side chain. In one embodiment of the present invention, its chemical structural formula is selected from one of formula (II), formula (III), formula (IV) or formula (V): Equation (II), Equation (III), Equation (IV), Equation (V); The chemical structural formula of R is shown in formula (VI): Formula (VI); The dashed line indicates that equation (VI) is connected to equation (II), equation (III), equation (IV), or equation (V).

[0011] The second objective of this invention is to provide a method for preparing an n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization, comprising the following steps: The reactants were mixed with thiophene side-chain monomers substituted with organotin compounds, and then a catalyst and a co-catalyst were added. The mixture was dissolved in a mixed solvent of chlorobenzene (CB) and N,N-dimethylformamide (DMF), mixed, and then subjected to Stille polycondensation. The reaction solution was then treated (the reaction solution was poured into n-hexane to precipitate, followed by Soxhlet extraction with acetone and n-hexane in sequence, and finally dried) to obtain an n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization. The reactants are selected from one of 4,4'-dibromo-2,2'-bipyridine, 4,4'-dibromo-2,2'-bipyridine, or a cationic acceptor monomer; The cationic acceptor monomer was prepared by the following method: After dissolving the precursor, a complex was added at room temperature for cyclization, utilizing the sp... 2 The lone pair electrons of the hybrid nitrogen atom undergo rapid coordination cyclization with boron, resulting in immediate precipitation. After cold filtration, washing, and drying, a cation acceptor monomer is obtained. The precursor is selected from 4,4'-dibromo-2,2'-bipyridine or 4,4'-dibromo-2,2'-bipyridine.

[0012] In one embodiment of the present invention, the catalyst is selected from one of tetra(triphenylphosphine)palladium, palladium acetate, (1,5-cyclooctadiene)palladium dichloride, tris(dibenzylideneacetone)palladium, or 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride. The co-catalyst is selected from one of cuprous iodide (CuI), silver iodide (AgI), or ferrous iodide (FeI2); The molar ratio of the reactants, the bis-organotin-substituted thiophene side-group DPP monomer, the catalyst, and the co-catalyst is 1:0.001~10:0.001~10; During the Stille polycondensation reaction, the temperature is 40~150 ℃ and the time is 5 min~72 h; The molar ratio of precursor to complex is 1:1 to 100; The complex is selected from one of boron trifluoride diethyl ether complex (BF3·Et2O) or boron trifluoride methanol complex (BF3·MeOH); During the cyclization reaction, the temperature ranges from 0 to 80 ℃, and the time ranges from 1 min to 72 h.

[0013] In one embodiment of the present invention, the preparation of an n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization is shown below: .

[0014] The third objective of this invention is to provide an application of an n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization in the preparation of porous thin films.

[0015] The fourth objective of this invention is to provide a porous thin film prepared by the above-mentioned n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization.

[0016] The fifth objective of this invention is to provide a method for preparing a porous thin film, comprising the following steps: The above-mentioned n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalization of the main chain was dissolved in a strong hydrogen bond donor solvent (hexafluoroisopropanol (HFIP)) and a poor solvent (dimethyl glycol ether (DME); the introduction of DME can regulate the degree of aggregation of polymer chain segments in the solution, so that while maintaining the porous microstructure, a relatively regular π-π pre-aggregate stacking occurs inside the porous network framework) to obtain a mixed solution; The mixed solution was spin-coated onto the substrate surface, and the solvent was locked in place by the hydrogen bond network formed between the fluorine atoms / fluorine cations in the polymer structure and the solvent. After thermal annealing, the solvent was released to obtain a porous film (a three-dimensional interconnected porous micro-nano network morphology was formed in place inside the film).

[0017] A sixth object of the present invention is to provide an application of the above-mentioned porous thin film in the fabrication of an n-type accumulator transistor, wherein the porous thin film serves as a transistor channel layer.

[0018] In this invention, the porous film exhibits geometrically normalized transconductance (GMT) under aqueous electrolyte conditions. g m,n >23.9 S cm -1 Material performance quality factor ( μC >109.0 F cm -1 V -1 s -1 .

[0019] The polymer possesses intrinsic mixed ion-electron dual conduction properties and exhibits high volumetric specific capacitance in aqueous or bioelectrolyte environments. C Reaching 200~581 F cm -3 ).

[0020] The seventh object of the present invention is to provide an n-type organic electrochemical transistor, which is prepared by the above-described porous thin film.

[0021] In one embodiment of the invention, the n-type organic electrochemical transistors (OECTs) possess record-breaking electrical characteristics: their normalized transconductance... g m,n Reaching 38.9 S cm -1 Quality factor μC Reaching 215.9 F cm -1 V -1 s -1 Volumetric capacitance C Increased to 581 F cm -3 .

[0022] The eighth object of the present invention is to provide an application of the above-mentioned n-type organic electrochemical transistor in the fabrication of a bioelectronic sensor.

[0023] The ninth objective of this invention is to provide a bioelectronic sensor prepared by the above-described n-type organic electrochemical transistor.

[0024] In one embodiment of the present invention, the bioelectronic sensor is a wearable electrocardiogram (ECG) sensor; in use, by attaching or conductively connecting the gate or channel layer of an n-type organic electrochemical transistor to the surface of human skin, the weak ionic electrical signal generated by the heartbeat is efficiently amplified and converted into a drain-source current signal output; the bioelectronic sensor has a high signal-to-noise ratio and excellent sensitivity.

[0025] Compared with the prior art, the present invention has the following beneficial effects: Synergistic construction of ion-electron transport channels: interconnected porous channels for aqueous biological ions (such as Na+). + Cl - It provides an almost unobstructed macroscopic fast track, enabling it to penetrate instantly to the entire active layer, greatly promoting charge storage capacity; while its ultra-dense π-π conjugate stacking ensures high-speed hopping conduction of electrons, which to some extent solves the problem of "a sharp drop in electron mobility when ion penetration increases" in traditional materials.

[0026] Excellent electrochemical transistor device performance: Organic electrochemical transistors (OECTs) constructed based on PBPzBF3 thin films processed in mixed solvents (MS) exhibit superior geometrically normalized transconductance. g m,n 38.9 S cm achievable -1 Volumetric capacitance C Increased to 581 F cm -3 Overall quality factor μC Up to 215.9 F cm -1 V -1 s -1 It is at a relatively high level among n-type OMIECs materials.

[0027] High-sensitivity biosensing applications: When the device of this invention is attached to human skin to construct an in vitro electrocardiogram (ECG) flexible sensor, it can amplify the weak potential generated by the heartbeat in situ without distortion into a significant drain-source current. The P peak, QRS complex wave and T peak in the waveform are extremely clear, with an ultra-high signal-to-noise ratio and operational stability. Attached Figure Description

[0028] Figure 1 Fine NMR and mass spectrometry characterization of key receptor monomers: (a) NMR and mass spectrometry characterization of monomers BPyBF3 and BPzBF3 1 (a) Comparison of H-spectrum; (b) Exhibiting typical characteristics of a four-coordinate boron center. 11B spectrum; (c) High-resolution matrix-assisted laser desorption / ionization time-of-flight mass spectra (MALDI-TOF MS) of BPzBF3 and (d) BPyBF3.

[0029] Figure 2 Density functional theory (DFT) calculation results for the material: (a) Evolution of surface electrostatic potential (ESP) of precursor and coordinated monomer, clearly showing the convergence of positive charges in the main chain; (b) Spatial distribution of frontier molecular orbitals and significantly downshifted LUMO level; (c) Regular planar conformation of conjugated framework.

[0030] Figure 3 For polymer (ab) solutions and thin films in the ultraviolet-visible-near-infrared (UV-) range. vis (-NIR) absorption spectrum, (ce) in-situ electrochemical ultraviolet absorption spectrum, and (f) frontier orbital level.

[0031] Figure 4 The transfer characteristics and transconductance curves of (a) PBPz, (b) PBPzBF3, (c) PBPy and (d) PBPyBF3 processed with a mixed solvent (MS, 10% DME) are shown.

[0032] Figure 5 For polymer integrated devices used in in vitro electrocardiogram (ECG) biosensing monitoring: (a) Layout diagram of human skin adhesion test; (b) Panoramic comparison of measured ECG waveforms and signal-to-noise ratio (SNR) between cationized PBPzBF3 devices and conventional PBPz devices. Detailed Implementation

[0033] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.

[0034] Unless otherwise specified, all reagents used in the following embodiments are commercially available reagents, and all detection methods and techniques used are conventional detection methods and techniques in the art.

[0035] Example 1 This embodiment provides a method for synthesizing the cationic acceptor monomer BPyBF3, and the synthetic route is shown in the following formula: In a strictly anhydrous and oxygen-free Schlenk reaction tube, the BPy precursor (5,5'-dibromo-2,2'-bipyridine, 0.3 g, 0.95 mmol, 1 eq.) was added to 5 mL of ultra-dry dichloromethane to obtain the BPy precursor solution; The above BPy precursor solution was heated at 40 °C with controlled stirring until the solid was completely dissolved. Using an airtight syringe, the boron trifluoride diethyl ether complex (BF3·Et2O, 2.77 g, 19.1 mmol, 20 eq.) was injected rapidly in one go to obtain the reaction solution. Due to the sp on the bipyridine ring 2 The lone pair electrons of the hybrid nitrogen atom have a very high complexation affinity with the strong Lewis acid boron center, and the reaction solution instantly changes from clear to turbid, producing a large amount of bright yellow precipitate; the reaction is carried out at 40 ℃ with continuous stirring for 2 hours. After the reaction was completed, the solid filter cake was collected by rapid filtration and washed three times with ice-cold anhydrous dichloromethane to completely remove unreacted BF3·Et2O. The solid obtained after washing was placed in a vacuum oven and dried at 60 °C for 12 h to finally obtain 120 mg of high-purity bright yellow powder target cation acceptor monomer: BPyBF3, with a yield of 33%.

[0036] Structural characterization and molecular weight determination data of BPyBF3 are as follows: Figure 1 As shown, the details are as follows: 1 H NMR (400 MHz, DMSO- d 6) δ = 8.83 (dd, J = 2.4, 0.8 Hz, 2H), 8.30(dd, J = 8.5, 0.8 Hz, 2H), 8.22 (dd, J = 8.5, 2.4 Hz, 2H). 13 C NMR (101 MHz, DMSO- d6 ) δ =153.07, 150.23, 140.25, 122.22, 121.29. 11 B NMR (128 MHz, DMSO- d6 δ = -0.46. 19 F NMR (376 MHz, DMSO- d 6) δ = -147.44, -166.06. MALDI-TOF MS ( M = 381.78): found m / z = 381.54 [M + ]. The electrostatic potential distribution of BPyBF3 is as follows Figure 2As shown in a, BPyBF3 has a stronger electron-withdrawing ability compared to the uncationized monomer.

[0037] Example 2 This embodiment provides a method for synthesizing the cation acceptor monomer BPzBF3, and the synthetic route is shown in the following formula: In a strictly anhydrous and oxygen-free Schlenk reaction tube, the BPz precursor (5,5'-dibromo-2,2'-bipyrazine, 0.2 g, 0.63 mmol, 1 eq.) was added to 5 mL of ultra-dry dichloromethane to obtain the BPz precursor solution; The above BPz precursor solution was heated at 40 °C and stirred under controlled temperature until the solid was completely dissolved. Using an airtight syringe, the boron trifluoride diethyl ether complex (BF3·Et2O, 1.80 g, 12.7 mmol, 20 eq.) was injected in a single, rapid injection to obtain the reaction solution. Due to the sp on the bipyridine ring 2 The lone pair electrons of the hybrid nitrogen atom have a very high complexation affinity with the strong Lewis acid boron center, and the reaction solution instantly changes from clear to turbid, producing a large amount of bright yellow precipitate; the reaction is carried out at 40 ℃ with continuous stirring for 2 hours. After the reaction was completed, the solid filter cake was collected by rapid filtration and washed three times with ice-cold anhydrous dichloromethane to completely remove unreacted BF3·Et2O. The solid obtained after washing was placed in a vacuum oven and dried at 60 °C for 12 h to finally obtain 97.1 mg of high-purity bright yellow powder target cation acceptor monomer: BPzBF3, with a yield of 40%.

[0038] Structural characterization and molecular weight determination data of BPzBF3 are as follows: Figure 1 As shown, the details are as follows: 1 H NMR (400 MHz, DMSO- d 6) δ = 9.27 (d, J = 1.4 Hz, 2H), 9.04 (d, J =1.4 Hz, 2H). 13 C NMR (101 MHz, DMSO- d 6) δ 146.87, 143.05, 141.55. 11 B NMR (128 MHz, DMSO- d 6) δ = -0.49. 19F NMR (376 MHz, DMSO- d 6) δ = -145.36, -147.41. MALDI-TOF MS ( M = 383.76): found m / z = 383.65 [M + ]. The electrostatic potential distribution of BPzBF3 is as follows Figure 2 As shown in figure a, compared to the uncationized monomer, BPzBF3 exhibits stronger electron-withdrawing ability; the electron cloud distribution of BPzBF3 is shown in figure a. Figure 2 As shown in b, the LUMO energy level decreases to -4.10 eV, and the electron cloud distribution becomes more uniform.

[0039] Example 3 This embodiment provides the preparation of an n-type organic ion-electron hybrid conductor material, PBPzBF3, based on boron-nitrogen coordination functionalized main chain cationization. The synthetic route is shown in the following formula: In a 15 mL well-sealed Schlenk reaction tube, equimolar amounts of the dual organotin donor monomer (95.0 mg, 57.9 μmol) and BPzBF3 prepared in Example 2 (22.2 mg, 57.9 μmol) were precisely weighed. In a highly purified nitrogen glove box, the main catalyst (tetra(triphenylphosphine)palladium, Pd(PPh3)4, 2.73 mg, 2.32 μmol, 4 mol%) and the co-catalyst (cuprous iodide, CuI, 0.5 mg, 2.32 μmol, 4 mol%) were added to the reaction tube. Subsequently, 2.4 mL of a mixture of anhydrous chlorobenzene (CB) and N,N-dimethylformamide (DMF), which had undergone rigorous degassing and deoxygenation treatment, was injected to obtain a mixed solution. In this embodiment, the chemical structural formula of the dual organotin donor monomer is shown below: ; .

[0040] Since the strong polar center of BPzBF3 is insoluble in conventional weakly polar solvents, the incorporation of polar DMF is crucial. The reaction tube was sealed and then placed in an oil bath at 135 °C to carry out Stille polymerization (15 min) in the dark. After the reaction was completed, the thick polymerization solution was quickly injected into 200 mL of n-hexane for reprecipitation, and the dark green solid was collected by centrifugation. The resulting dark green solid was transferred into a Soxhlet extractor and extracted sequentially with acetone and n-hexane for 24 h to thoroughly wash away residual monomers and residual tin and palladium reagents, yielding crude polymer. Finally, the crude polymer was collected by Soxhlet extraction with high-purity hexafluoroisopropanol (HFIP), the solvent was removed under reduced pressure, and the mixture was vacuum dried (60 °C) for 24 h to obtain an n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization: PBPzBF3, with a yield of 95%. Figure 2 As shown in c, density functional analysis indicates that the PBPzBF3 molecular skeleton has a very flat conformation with a twist angle of 0°.

[0041] Comparative Example 1 This comparative example is the same as Example 3 except that “BPzBF3” is replaced with “BPz”. The product PBPz in this comparative example had a yield of 97%.

[0042] Example 4 This embodiment is the same as embodiment 3 except that “BPzBF3” is replaced with “BPyBF3”. The product of this embodiment is PBPyBF3, with a yield of 95%. Figure 2 As shown in c, density functional analysis indicates that the PBPy molecular skeleton is more twisted, with a twist angle of 22°.

[0043] Comparative Example 2 This comparative example is the same as Example 3 except that “BPzBF3” is replaced with “BPy”. The product PBPy in this comparative example had a yield of 90%.

[0044] Figure 3 The photophysical and electrochemical properties of polymers. For example... Figure 3 As shown in a and 3b, the ultraviolet-visible-near-infrared (UV-) vis The NIR absorption spectrum exhibits a typical two-band absorption characteristic: the absorption band between 500 and 700 nm corresponds to the intramolecular charge transfer (ICT) process, while the absorption band between 300 and 450 nm corresponds to the π-π process. Transition. After B←N coordination cationization, the maximum absorption peak showed a slight blue shift, attributed to the enhanced electron-deficient properties of the B←N functional group. Upon transition from the solution state to the film state, the maximum absorption peak showed a significant red shift (>110 nm), and vibrational fine structure appeared. This indicates that the polymer chains underwent a certain degree of pre-aggregation during film formation, which is beneficial for forming a properly ordered microstructure. Spectroelectrochemical measurements were performed using a three-electrode system (with Ag / AgCl as the reference electrode). Figure 3 PBPy exhibits p-type doping behavior, while PBPyBF3, PBPz, and PBPzBF3 exhibit n-type transport behavior. Upon application of voltage, all polymers exhibit characteristic electrochemical doping behavior: the ICT absorption band intensity gradually decreases (electrochemical bleaching), while a polaron absorption band appears in the 900–1200 nm region. The results indicate that cationization of the main chain using B←N coordination enhances the doping ability of the polymer films. Cyclic voltammetry was used to evaluate the frontier molecular orbital energy levels of this series of polymers. The LUMO / HOMO energy level diagram is shown below. Figure 3 As shown in f. The results indicate that replacing pyridine with pyrazine (i.e., increasing sp) 2 The number of hybrid nitrogen atoms can effectively lower both the LUMO and HOMO energy levels simultaneously. The LUMO energy level is lowered by more than 0.30 eV, while the HOMO energy level is lowered by more than 0.15 eV. After forming a B←N coordinating cation, the LUMO energy level shifts further significantly, by 0.06 to 0.13 eV. However, the HOMO energy level remains almost unchanged. This indicates that main-chain cationization using B←N functionalization has a more significant impact on the LUMO energy level, while the HOMO energy level remains essentially unchanged due to the influence of counterions.

[0045] Example 5 This embodiment provides a method for constructing in-situ porous, highly crystalline thin films based on a mixed solvent (MS) processing strategy, as detailed below: Pure hexafluoroisopropanol (HFIP) was mixed with dimethyl ethylene glycol (DME), a medium-boiling-point solvent with poor polarity, to obtain a mixed solution (the volume ratio of HFIP to DME was 9:1). The PBPzBF3 prepared in Example 3 was dissolved in a mixed solution to obtain a concentration of 5 mg / mL. -1 Clarified polymer stock solution: PBPzBF3 solution; The PBPzBF3 solution was thoroughly agitated and ultrasonically mixed to form a mixed-solvent (MS) thin film processing system.

[0046] The above PBPzBF3 solution was spin-coated onto a clean Si / SiO2 substrate at room temperature (1500 rpm for 60 s). During the spin-coating process, some solvent molecules were locked in situ inside the liquid film due to the binding of the hydrogen bond network. It was then transferred to a hot plate and heat-annealed at 80 °C for 10 minutes to obtain a porous film. As the temperature rises, the hydrogen bond network between the polymer and the solvent rapidly dissociates, and the locked solvent molecules evaporate violently upon heating and escape from the interior of the film, thus leaving a high-density, large-area, interconnected three-dimensional micro-nano porous network morphology in situ inside the solid film.

[0047] Example 6 This embodiment provides the fabrication of high-performance n-type organic electrochemical transistors (OECTs), as detailed below: OECT device fabrication: A patterned gold source / drain electrode array with a thickness of 80 nm was pre-deposited on a 2 cm × 2 cm Si / SiO2 substrate using photolithography; the transistor channel dimensions were precisely determined as follows: channel length... L =80 μm, channel width W =2400 μm.

[0048] The mixed solvent processing strategy described in Example 5 was used in four groups: ①PBPzBF3 group: PBPzBF3 solution was spin-coated onto the channel region and annealed to obtain a porous crystalline active layer film with a thickness of 51.4 ± 1.7 nm; Add one drop of 0.1 M standard phosphate-buffered saline (PBS) solution in situ above the channel area as an electrolyte.

[0049] ②PBPyBF3 group: PBPyBF3 solution was spin-coated onto the channel region and annealed to obtain a porous, highly crystalline active layer film with a thickness of 46.6 ± 2.7 nm; Add one drop of 0.1 M standard phosphate-buffered saline (PBS) solution in situ above the channel area as an electrolyte.

[0050] ③PBPz group: PBPz solution was spin-coated onto the channel region and annealed to obtain a porous, highly crystalline active layer film with a thickness of 48.1 ± 1.1 nm; Add one drop of 0.1 M standard phosphate-buffered saline (PBS) solution in situ above the channel area as an electrolyte.

[0051] ④PBPy group: PBPy solution was spin-coated onto the channel region and annealed to obtain a porous, highly crystalline active layer film with a thickness of 55.9 ± 2.8 nm; Add one drop of 0.1 M standard phosphate-buffered saline (PBS) solution in situ above the channel area as an electrolyte.

[0052] A standard commercial Ag / AgCl electrode with extremely stable potential was inserted into the electrolyte as the gate. The device underwent routine transfer and output characteristic curve scanning using a Keysight B1500A semiconductor parameter analyzer, with the drain-source voltage fixed. V D = 0.6 V, making the gate voltage V G Scan from 0 V to 1.0 V; results as follows Figure 4 As shown in Table 1, the data summarize that PBPzBF3 exhibits the best organic electrochemical transistor performance, with its geometrically normalized maximum transconductance... g m,n Up to 38.9S cm -1 Component quality factor μC Up to 215.9 F cm -1 V -1 s -1 .

[0053] Figure 4 The transfer characteristic curves and transconductance curves of PBPz, PBPzBF3, PBPy and PBPyBF3 are shown, where PBPy exhibits hole transport characteristics, and PBPz, PBPzBF3 and PBPyBF3 exhibit electron transport characteristics.

[0054] Table 1. Performance of organic electrochemical transistors PBPy, PBPyBF3, PBPz, and PBPzBF3 a Thin film thickness, b Geometrically normalized maximum transconductance c Component quality factor d Volume capacitance e Current switching ratio Two n-type materials, PBPz and PBPzBF3, were selected for fabricating an OECT-based extracorporeal electrocardiogram (ECG) sensor. Figure 5 As shown in Figure a, commercially available electrodes were used to acquire cardiac electrical signals. Subjects wore commercially available electrodes (connected to the OECT gate) near the heart and grounded commercially available electrodes distally. The acquired cardiac signals modulated the conductivity of the OECT semiconductor layer, and the source-drain current changes over time were recorded. Results are shown below. Figure 5 As shown in b, the electrical signals generated by cardiac activity are reliably recorded and exhibit the expected waveform characteristics. To compare the sensitivity and signal-to-noise ratio (SNR) of the two materials, key signal parameters were extracted. I on / Ioff and I peak-to-peak ) and summarized in Figure 5 c. The PBPzBF3-based ECG sensor exhibits a higher on / off ratio and larger [performance / performance]. I peak-to-peak The value indicates that it has better sensitivity and a higher signal-to-noise ratio, thus enabling the acquisition of clearer electrocardiogram signals.

[0055] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the interpretation of the present invention, without departing from the scope of the invention, should be within the protection scope of the present invention.

Claims

1. An n-type organic ionic-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization, characterized in that, It has a conjugated backbone main chain composed of alternating copolymerization of electron acceptor units and electron donor units, and its chemical structural formula is shown in formula (I): Formula (I); Where X and Y are each independently selected from carbon, nitrogen, oxygen or sulfur; Z is selected from fluorine, chlorine, bromine or cyano; Ar represents aryl, heteroaryl or other conjugated groups; n represents the degree of polymerization of the polymer; The number-average molecular weight of n-type organic ion-electron hybrid conductor materials is >10 kDa.

2. The n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization according to claim 1, characterized in that, Its chemical structural formula is selected from one of formula (II), formula (III), formula (IV) or formula (V): Equation (II), Equation (III), Equation (IV), Equation (V); The chemical structural formula of R is shown in formula (VI): Formula (VI); The dashed line indicates that equation (VI) is connected to equation (II), equation (III), equation (IV), or equation (V).

3. A method for preparing an n-type organic ionic-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization as described in any one of claims 1 to 2, characterized in that, Includes the following steps: The reactants were mixed with thiophene side-chain monomers with dual organotin substitution, and then a catalyst and a co-catalyst were added. After dissolution, the mixture was mixed and subjected to Stille polycondensation. The post-treatment yielded an n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization. The reactants are selected from one of 4,4'-dibromo-2,2'-bipyridine, 4,4'-dibromo-2,2'-bipyridine, or a cationic acceptor monomer; The cationic acceptor monomer was prepared by the following method: The precursor was dissolved and added to the complex for cyclization, followed by post-treatment to obtain the cationic acceptor monomer. The precursor is selected from one of 4,4'-dibromo-2,2'-bipyridine or 4,4'-dibromo-2,2'-bipyridine; The catalyst is selected from one of tetra(triphenylphosphine)palladium, palladium acetate, (1,5-cyclooctadiene)palladium dichloride, tris(dibenzylideneacetone)palladium, or 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride. The co-catalyst is selected from one of cuprous iodide, silver iodide, or ferrous iodide; The molar ratio of the reactants, the thiophene side-chain monomer with dual organotin substitution, the catalyst, and the co-catalyst is 1:0.001~10:0.001~10; During the Stille polycondensation reaction, the temperature is 40~150 ℃ and the time is 5 min~72 h; The molar ratio of precursor to complex is 1:1 to 100; The complex is selected from one of boron trifluoride diethyl ether complex and boron trifluoride methanol complex; During the cyclization reaction, the temperature ranges from 0 to 80 ℃, and the time ranges from 1 min to 72 h.

4. The application of an n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization as described in any one of claims 1 to 2 in the preparation of porous thin films.

5. A porous thin film, characterized in that, The material was prepared using the n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization as described in any one of claims 1 to 2.

6. A method for preparing a porous thin film as described in claim 5, characterized in that, Includes the following steps: An n-type organic ion-electron hybrid conductor material based on boron-nitrogen coordination functionalized main chain cationization was dissolved in a strong hydrogen bond donor solvent and a poor solvent to obtain a mixed solution. The mixed solution was spin-coated onto the substrate surface and then thermally annealed to obtain a porous film.

7. The application of the porous thin film as described in claim 6 in the fabrication of an n-type accumulation transistor, characterized in that, The porous thin film serves as the transistor channel layer.

8. An n-type organic electrochemical transistor, characterized in that, The porous film described in claim 5 is prepared.

9. The application of the n-type organic electrochemical transistor as described in claim 8 in the fabrication of a bioelectronic sensor.

10. A bioelectronic sensor, characterized in that, It is prepared by the n-type organic electrochemical transistor according to claim 9.